2016
DOI: 10.1177/1687814016637329
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of gas–liquid flow in T-junction microchannels with different inlet orientations

Abstract: In this study, a comparative analysis of two-phase flow in T-junction microchannels with different inlet orientations was carried out. Based on computational fluid dynamics and the volume-of-fluid model, bubble size, bubble velocities, and pressure distributions were analyzed. The numerical algorithm was validated with the experimental observations from former literatures; the results show that when the capillary number, Ca, is low, the length of gas and liquid slug in the symmetric T-junction is higher than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…3 shows the four mesh types mentioned above along with their corresponding volume fraction contours, for the corresponding process circumstance of 𝑊𝑒 𝑖𝑛 = 0.003, 𝐶𝑎 𝑖𝑛𝑡 = 0.6, and 𝑅𝑒 𝑜𝑢𝑡 = 30. As noted by previous researchers (Bashir et al 2011;Liu et al 2016), the size of the elements used does not have a notable influence on the interface or the mechanism of breakup. Table 3 provides details about various meshes used in the study, including their statistics and the inner droplet diameter as shown in Fig 3 . This table confirms the claim made in the study that mesh independence is achieved, as the inner droplet diameter only shows a 1% variation between the smallest and greatest mesh resolutions.…”
Section: Grid Convergence Testmentioning
confidence: 51%
“…3 shows the four mesh types mentioned above along with their corresponding volume fraction contours, for the corresponding process circumstance of 𝑊𝑒 𝑖𝑛 = 0.003, 𝐶𝑎 𝑖𝑛𝑡 = 0.6, and 𝑅𝑒 𝑜𝑢𝑡 = 30. As noted by previous researchers (Bashir et al 2011;Liu et al 2016), the size of the elements used does not have a notable influence on the interface or the mechanism of breakup. Table 3 provides details about various meshes used in the study, including their statistics and the inner droplet diameter as shown in Fig 3 . This table confirms the claim made in the study that mesh independence is achieved, as the inner droplet diameter only shows a 1% variation between the smallest and greatest mesh resolutions.…”
Section: Grid Convergence Testmentioning
confidence: 51%
“…The contact angle used with wall adhesion affects the composition of the bubbles. The chosen contact angle for the air phase's confluence with the water phase was 36º, that being compatible with the interface, as describe by in (Pham et al 2012) [31] and (Liu et al 2016) [32].…”
Section: Modelling Assumptionsmentioning
confidence: 99%
“…Commonly, the primary phase is a continuous medium and a major component of the fluid. The secondary phase is a minority phase dispersed in the main phase [22], [23]. For the sake of investigating the multiphase flow, Volume of Fluent (VOF) model, Mixture model and Eulerian model are developed and integrated in Fluent software.…”
Section: Multiphase Flow Modelmentioning
confidence: 99%